Pengujian Kincir Air Hidrokinetik Undershoot Di Irigasi Limau Manis Padang - Ruzita Sumiati; Fardinal Fardinal; Nusyirwan Nusyirwan; Adriansyah Adriansyah; Robby Novrizal (Jurnal Teknik Mesin, 2019)
The power produced by a hydrokinetic turbine depends on the interaction between the rotor and water. Therefore, the optimal rotor geometry must be designed and built to capture maximum water energy and convert it into usable energy. Hydropower is one of the potential renewable energy that can contribute to the need for electricity. Hydropower generator is pollution free so this generator can answer environmental problems and the availability of renewable energy sources. The aim to be achieved in this study is to produce a turbine hydropower with good performance if it operates on an irrigation channel and is applied as a power plant. This research was developed to get the right specifications for the use of hydrokinetic turbines in the irrigation canal area. There are several methods carried out in the design of hydrokenetic turbines, namely by designing blades based on the shape of water flow, repairing the transmission system, and selecting the right generator. In this study, we tested the sweet lemon irrigate applied and tested in the area of ​​Padang Sumbar Sweet Limes Pauh, the results obtained were that the turbine can produce power of about 12.6 watts.